Kajian Teknis Geometri Jalan Tambang untuk Mengurangi Dampak Slippery sebagai Upaya Meningkatkan Produksi Nikel PT ANTAM (Persero) Tbk di Kecamatan Maba, Kabupaten Halmahera Timur, Provinsi Maluku Utara - Sandy Herdiansyah; Zaenal; Iswandaru (Bandung Conference Series: Mining Engineering, 2022)
Abstract. PT Aneka Tambang Tbk nickel production located in Wayafli Village, Maba District, East Halmahera Regency, North Maluku Province, to support the mining process, the Tanjung Buli site uses a conveyance with the type of Articulated Dump Truck CAT 745 and Volvo FMX 440 8X4 with a Volvo EC480EL loading and unloading tool, one of the obstacles at the Tanjung Buli site is the geometry of the road and the duration of slippery This research aims to be able to find out the condition of the transport road and activities slippery handling, Based on research, the condition of the road geometry which includes the actual road width condition of the straight condition has the smallest width of 5,944 - 20,329 meters with the condition of the bend road has a size of 6.201- 30.714 meters, with the highest grade being 19% for the actual superelevation of a maximum of 7.2%, the standard grade used is 12% and after calculations, the minimum superelevation value is 6% Based on the productivity of the support tool for support tools for support tools The CAT D6RXL bulldozer is 147.40 m3/h and the Komatsu D85ESS-2A is 189.27 m3/h. The total slippery handling duration in the pre-production area of 72.51 minutes can be reduced by repairing the transport road, especially in the crossfall section to be able to drain rainwater so that there is no inundation, it can reduce the duration of 44.61 minutes, then by adding a bulldozer unit the duration can be reduced to 29.74 minutes and changing the pushing method to side by side dozing to 29.45 minutes. Abstrak. PT Aneka Tambang Tbk produksi nikel yang terletak di Desa Wayafli Kecamatan Maba Kabupaten Halmahera Timur Provinsi Maluku Utara, untuk menunjang proses penambangan, site Tanjung Buli menggunakan alat angkut dengan jenis Articulated Dump Truck CAT 745 dan Volvo FMX 440 8X4 dengan alat gali muat Volvo EC480EL salah satu hambatan yang ada pada site Tanjung Buli adalah geometri jalan serta durasi slippery Penelitian ini memiliki tujuan untuk dapat mengetahui kondisi jalan angkut dan kegiatan penanganan slippery, Berdasarkan penelitian, kondisi dari geometri jalan yang termasuk kondisi lebar jalan aktual kondisi lurus memiliki lebar terkecil 5,944 - 20,329 meter dengan kondisi jalan tikungan memiliki ukuran 6,201- 30,714 meter, dengan grade tertinggi adalah 19% untuk superelevasi actual maksimal 7,2%, standart grade yang digunakan adalah 12% dan setelah dilakukan perhitungan, nilai superelevasi minimum adalah 6% Berdasarkan produktivitas dari alat support untuk alat support Bulldozer CAT D6RXL sebesar 147,40 m3/jam dan Komatsu D85ESS-2A sebesar 189,27 m3/jam. Durasi penanganan slippery total pada areal pra-produksi sebesar 72,51 menit dapat dikurangi dengan cara memperbaiki jalan angkut terutama pada bagian crossfall untuk dapat mengalirkan air hujan agar tidak terjadi genangan dapat mengurangi durasi 44,61 menit, lalu dengan menambah unit bulldozer durasi dapat berkurang menjadi 29,74 menit dan mengganti metode pendorongan menjadi side by side dozing menjadi 29,45 menit.